Temporal Control of Membrane Fusion through Photolabile PEGylation of Liposome Membranes. (9th December 2015) - Kong, Li; Askes, Sven H. C.; Bonnet, Sylvestre; Kros, Alexander; Campbell, Frederick
Abstract: Membrane fusion results in the transport and mixing of (bio)molecules across otherwise impermeable barriers. In this communication, we describe the temporal control of targeted liposome–liposome membrane fusion and contents mixing using light as an external trigger. Our method relies on steric shielding and rapid, photoinduced deshielding of complementary fusogenic peptides tethered to opposing liposomal membranes. In an analogous approach, we were also able to demonstrate precise spatiotemporal control of liposome accumulation at cellular membranes in vitro.